Existence of а multiplicative basis for a finitely spaced module over an aggregate - Roiter, A.V.; Sergeichuk, V.V. (Український математичний журнал, 1994)
It is proved that a finitely spaced module over a k-category admits a multiplicative basis such a module gives to a matrix problem, in which the allowed column transformations are determined by a module structure, the row transformations are arbitrary, and the number of canonical matrices is infinite. Доведено, що скінченно зображувальний модуль над k-категорією (який можна зв'язати з матричною задачею, стовпцеві перетворення якої задаються модульною структурою, рядкові довільні та існують лише скінченне число матриць канонічного вигляду) має мультиплікатний базис. We study the minimality of the elements χh,j,kχh,j,k of the canonical system of root vectors.